Local acoustic-prosodic entrainment in European Portuguese - Cabarrão, Vera (2019)
This paper presents an acoustic-prosodic analysis of entrainment in map-task dialogues in European Portuguese. Our main goal is to analyze how turn-by-turn entrainment varies with distinct structural metadata events: types of sentence-like units (SUs) in consecutive turns (e.g. interrogatives followed by declaratives, or both declaratives), and with the presence of discourse markers, affirmative cue words, and disfluencies in the beginning of turns. Results show that entrainment at turn-exchanges occurs in terms of pitch, energy, duration, and voice quality. Considering SUs types, question-answer pairs are the ones with stronger similarity, as declarative-interrogative turns are the ones where less entrainment occurs. Moreover, in question-answer pairs, Yes/No and Tag questions present stronger evidences of entrainment than Wh- questions. Regarding turn-initial structures, there are evidences of (i) stronger entrainment when the second turn begins with an affirmative cue word, (ii) less strong with ambiguous structures (such as ‘OK’), emphatic affirmative answers, and negative cue words; (iii) and scarce with disfluencies and discourse markers. Different degrees of local entrainment may be related to the informative structure of distinct structural metadata events.